French-language road cinema : borders, diasporas, migration and 'New Europe' - Gott, Michael (Traditions in world cinema., 2016)
An examination of contemporary French-language road movies within the cultural and political context of 'New Europe'. Over the past two decades road cinema has become an increasingly popular form of expression for European directors. Focusing on a corpus of films from France, Belgium and Switzerland, including works by Ismañl Ferroukhi, Bouli Lanners, Aki KaurismÃÞki and Jacqueline Audry amongst many others, French-language Road Cinema contends that nowhere is the impulse to remap the spaces and identities of 'New Europe' more evident than in French-language cinema. Drawing on mobility studies, cultural geography and film theory, this innovative work sketches out the flexible yet distinctive parameters of contemporary French-language road cinema, and argues for an understanding of the 'road movie' not as a genre but as a thematic and formal template that crosses cinematic categories to bring together a wide array of films that narrate the movements of migrants, tourists and business executives. Key Features. The first monograph to focus on transnational French-language (from or co-produced by France, Belgium and Switzerland) European road cinema Each chapter analyses key formal characteristics of a carefully chosen selection of films through the optic of a significant cultural or political issue facing 'New Europe' Examines the unique formal and thematic qualities of French-language European road movies in relationship to American and European traditions Case studies examine well-known films, as well as those that have not yet received scholarly attention but are commercially available with English subtitles Compares and contrasts more positive vantage points on cinematic mobility with recent migrant cinema